IMPROVING THE STORAGE LIFE AND MARKETABILITY OF MATURE ORANGE CAPE GOOSEBERRY FRUIT: ENHANCEMENT OF THE ENZYMATIC ANTIOXIDANT SYSTEM UNDER EXOGENOUS MELATONIN TREATMENT - Taghipour, Leila (Journal of Agricultural Sciences (Belgrade), 2025)
The cape gooseberry fruit (Physalis peruviana L.) is a climacteric fruit that experiences significant color and texture changes during storage due to increased ethylene synthesis. While its storage life is one month with its calyx, it only lasts 4 to 5 days without it. Therefore, strategies to reduce postharvest losses and extend storage life are essential. In this study, entirely ripe orange cape gooseberry fruits with yellow calyces were harvested from a commercial greenhouse in Pasargad (Fars province, Iran) and transferred to the laboratory. After washing, fruits were immersed in melatonin solutions at concentrations of 100, 200, and 300 µM for 5 minutes, with distilled water as the control. The fruits were stored at 10 °C and 90 ± 5% relative humidity for 21 days and evaluated weekly. Results showed that all melatonin treatments significantly controlled weight loss and fruit softening. Melatonin-treated fruits also had comparable taste indices and performed better than controls. Treatment with melatonin improved the antioxidant enzymatic system, with fruits treated with 300 µM melatonin showing the highest activities of superoxide dismutase, catalase, ascorbate peroxidase, and peroxidase enzymes, and the lowest hydrogen peroxide content, indicating reduced oxidative stress. Additionally, the lowest decay (17.4%) was in fruits treated with 300 µM melatonin, while the highest decay (43.83%) was in control fruits. Melatonin treatment proved effective in improving the quality and extending the shelf life of cape gooseberry fruits, acting as a valuable and environmentally friendly postharvest preservation method by delaying ripening, enhancing antioxidant activity, and preserving taste indices.